Mallomonas cattiensis, sp. nov. (Synurales, Chrysophyceae), a new species from Viet Nam - Gusev, Evgeniy Sergeevich; Doan-Nhu, Hai; Nguyen-Ngoc, Lam (Phytotaxa, 2015)
Mallomonas cattiensis, sp. nov. is described from Ta Lai reservoir, located in Cat Tien National Park (Dong Nai Province, Southeastern Viet Nam). The description is based on silica-scale morphology studied by means of transmission and scanning electron microscopy. This new species has thick, heavily silicified tripartite scales. The most remarkable features of the new taxon are thick secondary layer in form of lobate structures on the anterior flange of the scales and wide proximal border, covering the posterior flange and often overlapping the V-rib. Mallomonas cattiensis belongs to the section Mallomonas and is most morphologically similar to Mallomonas morrisonensis.